2021
DOI: 10.1002/num.22782
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the parareal approach based on discontinuous Galerkin method for time‐dependent Stokes equations

Abstract: This paper analyzes a parareal approach based on discontinuous Galerkin (DG) method for the time-dependent Stokes equations. A class of primal discontinuous Galerkin methods, namely variations of interior penalty methods, are adopted for the spatial discretization in the parareal algorithm (we call it parareal DG algorithm). We study three discontinuous Galerkin methods for the time-dependent Stokes equations, and the optimal continuous in time error estimates for the velocities and pressure are derived. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is an attractive property, but it is also the main difficulty since the temporary accuracy should more or less match the spatial accuracy. A first numerical result has suggested that if the time discretization is under-resolved, then the spatial superconvergence will be concealed, see [15]. In this paper, we first demonstrate that for the high-order case (p ≥ 2), to benefit from the spatial superconvergence, explicit Runge-Kutta methods will suffer from an extremely small time step.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…It is an attractive property, but it is also the main difficulty since the temporary accuracy should more or less match the spatial accuracy. A first numerical result has suggested that if the time discretization is under-resolved, then the spatial superconvergence will be concealed, see [15]. In this paper, we first demonstrate that for the high-order case (p ≥ 2), to benefit from the spatial superconvergence, explicit Runge-Kutta methods will suffer from an extremely small time step.…”
Section: Introductionmentioning
confidence: 69%
“…The main focus of this paper is the SDG method, which has been introduced recently by Li, Benedusi and Krause [15]. The SDG method is an iterative method derived from the DG method for time discretization, with the order of accuracy increased by one for each additional iteration.…”
Section: The Sdg Methodsmentioning
confidence: 99%
See 3 more Smart Citations